Sintering of Calcium Aluminate - Singh V.K. (My University, 2025)
Measurements of initial sintering shrinkage of CaAl4O7are reported in the temperature range 1380°-1480°C. The particle size chosen was—45 micron and the soaking periods were from 10 to 180 minutes. The time dependance of shrinkage indicated that the grain boundary diffusion is the dominant mechanism of sintering. The activation energy for the sintering of CaAl4O7 was found to be 151.0 k cal.mol−-1. © 1996 Taylor and Francis Group, LLC.